2017
DOI: 10.1002/jmv.24978
|View full text |Cite
|
Sign up to set email alerts
|

Daclatasvir and asunaprevir treatment in patients infected by genotype 1b of hepatitis C virus with no or subtle resistant associated substitutions (RAS) in NS5A‐Y93

Abstract: In this study, we investigated the real-world data of the first approved interferon-free regimen in Japan, daclatasvir and asunaprevir (DCV+ASV), in chronic hepatitis C patients infected HCV genotype 1b with no or subtle amount of baseline resistant associated substitutions (RAS). Among 924 patients registered in our multicenter study, 750 patients who were proven not to be infected with NS5A-Y93H RAS by direct sequencing and to have no or subtle amount (less than 20%) of NS5A-Y93H RAS by probe assays (Cycleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…In 2017, a Japanese multicenter study was published about the use of ASV and DSV for recurrence of HCV after liver transplantation, where an SVR12 rate of 80.3% was achieved[ 23 ]. According to the authors this SVR rate was unsatisfactory, and indeed in other patient studies in the pre-transplant setting higher SVR rates were reported[ 21 , 24 , 25 ]. A meta-analysis of 41 studies showed a pooled SVR rate of 89.9% for HCV genotype 1[ 26 ].…”
Section: Introductionmentioning
confidence: 90%
“…In 2017, a Japanese multicenter study was published about the use of ASV and DSV for recurrence of HCV after liver transplantation, where an SVR12 rate of 80.3% was achieved[ 23 ]. According to the authors this SVR rate was unsatisfactory, and indeed in other patient studies in the pre-transplant setting higher SVR rates were reported[ 21 , 24 , 25 ]. A meta-analysis of 41 studies showed a pooled SVR rate of 89.9% for HCV genotype 1[ 26 ].…”
Section: Introductionmentioning
confidence: 90%